Adaptation to Climate Change via Adjustment in Land Leasing: Evidence from Dryland Wheat Farms in the U.S. Pacific Northwest - Hongliang Zhang; Jianhong E. Mu; Bruce A. McCarl (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
This paper investigates how dryland wheat farm operators adapt to climate through the use of land leasing in the U.S. Pacific Northwest region. Using a farm-level dataset from the U.S. Census of Agriculture, we build a statistical relationship between climate and leased acreage for dryland wheat farms. We find that a warmer and wetter climate reduces leased dryland wheat farmland, suggesting that land leasing is a potential strategy for adaptation to future climate. Using climate projections from 20 global climate models, we predict that, by 2050, leased acreage for dryland wheat farms on average will decline by 23% and 29% relative to 2012 levels under the medium and high greenhouse gas emission scenarios, respectively.
Keywords: Q15; Q54; C21; 330; Land Leasing; Climate; Climate Change Adaptation; Wheat